Effects of goal orientation on environment management in technology-based physics learning - Yang, Yanchao; Du, Jianxia; Teo, Timothy; Xue, Sijia; Liu, Fangtong (Frontiers in Psychology, 2023)
The purpose of the current study is to propose and examine a comprehensive model that uses motivational and self-regulated variables to explain factors affecting environment management in technology-based physics learning among Chinese secondary school students. Data were collected from 726 grade-eight secondary school students in Southeast China, who were learning physics. Structural equation modeling was used to analyze the relationships among students’ goal orientations, environment management, and time management. Results suggest that students were more likely to manage their environment if they had learning-oriented goals and if they managed their time, but they were less likely to do so if they had social-oriented goals. Implications for teachers’ technology integration in physics class were discussed.